Development of Chemistry Subject Module to Improve Student’s Critical Thinking in SMA Negeri 1 Pulau-Pulau Terselatan Southwest Maluku - Dahoklory, Sendry Richard; Riyanto, Yatim; Prasetya, Sukma Perdana (Universitas Malikussaleh, 2019)
The study aims to develop the chemistry subject module and its effectiveness in learning to improve students' critical thinking. It was conducted on the students of class XI in SMA Negeri 1 Pulau-Pulau Terselatan Southwest Maluku. It is the research of development which uses the Borg and Gall (2003) model, who adapted Dick and Carey's model named Instructional System Design which includes ten stages of development. The product of this development research is the chemistry subject module for the lesson about the colloidal system. Afterward, the developed module gets validation test using questionnaires that are given to the experts and the users, to know its feasibility to use in learning. Then, the results indicate that it is in the criteria of very feasible to use in learning. After get validation, it is analyzed using Normalized Gain (N-gain) to determine its effectiveness to improve students' critical thinking. The analysis data is obtained through one group pre-test and post-test design. Then, the result of N-gain analysis is 0.74 categorized as “High” means that there is an increase in students' critical thinking after the application of the module. Thus it can be concluded that the chemistry subject module is suitable for use in learning, and it influences the effectiveness of learning since it can effectively improve students' critical thinking in SMA Negeri 1 Pulau-Pulau Terselatan Southwest Maluku.